2019
DOI: 10.3390/w11051044
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Red Tide Monitoring Method using Sentinel-2 Data for Sustainable Management of Brackish Lake Koyama-ike, Japan

Abstract: We proposed and validated a method for monitoring red tides in the brackish Lake Koyama-ike, Japan, using Sentinel-2 Multispectral Instrument (MSI) data with a 10 m spatial resolution. To achieve this objective, we acquired 36 spectral reflectance/Chla data points in the field from 2012 to 2018. We obtained a high correlation of Chla (R2 = 0.83) using the proposed red tide model (RIKY = [MSI Band 5 – MSI Band 4]/[MSI Band 5 + MSI Band 4]) and field data. Based on our results, the proposed model was also valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The prominent reflectance peak located in the 700–720 nm region shifts towards longer wavelengths as phytoplankton concentrations increase; thus, these bands are suggested as the best option for HABs mapping ( Toming et al, 2016 ). Sakuno et al (2019) already indicated the potential of the 704 nm red-edge band of S2 for red tide monitoring in Japan. The sensitivity of NDCI to chl-a concentration in turbid productive waters has been demonstrated, as well as its potential application to several platforms and diverse environments, producing minimal uncertainty ( Mishra and Mishra, 2012 ).…”
Section: Discussionmentioning
confidence: 98%
“…The prominent reflectance peak located in the 700–720 nm region shifts towards longer wavelengths as phytoplankton concentrations increase; thus, these bands are suggested as the best option for HABs mapping ( Toming et al, 2016 ). Sakuno et al (2019) already indicated the potential of the 704 nm red-edge band of S2 for red tide monitoring in Japan. The sensitivity of NDCI to chl-a concentration in turbid productive waters has been demonstrated, as well as its potential application to several platforms and diverse environments, producing minimal uncertainty ( Mishra and Mishra, 2012 ).…”
Section: Discussionmentioning
confidence: 98%
“…The prominent reflectance peak located in the 700-720 nm region shifts towards longer wavelengths as phytoplankton concentrations increase; thus, the 704 nm band is suggested as the best option for HABs mapping 19 . Sakuno et al already indicated the potential of the 704 nm red-edge band of S2 for red tide monitoring in Japan 21 . The sensitivity of NDCI to chl-a concentration in turbid productive waters has been demonstrated, as well as its potential application to several platforms and diverse environments producing minimal uncertainty 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to ocean colour sensors, land-focused sensors, which have higher spatial resolution, can be applied. The latest generation of satellites such as the twin Sentinel-2A/B (S2) satellites of the European Union's Copernicus earth observation programme, carry the MSI (MultiSpectral Instrument) sensor, whose bands have valuable applications for phytoplankton estimation [17][18][19] and algal bloom detection 20,21 . The mission was initially designed for the evaluation of urban planning and terrestrial ecosystems, but the incorporation of bands in the red-edge spectrum (704, 740, and 783 nm; see Supplementary Table S1), its radiometric quality (12 bits), its high-revisit frequency (5 days at the equator), and its high spatial resolution (10 m) have proven its utility for coastal and inland waters examination 18,19,22 .…”
mentioning
confidence: 99%
“…The footprint of many of the remote-sensing sensors cover large areas with high temporal resolution; thus, they can potentially capture the spatial and temporal variabilities of HABs, as evidenced by the extensive literature describing the detection, monitoring, and forecasting of HABs using remote sensing-based techniques and sensors [9]. Investigations utilizing moderate-resolution imaging spectroradiometers (MODIS-Aqua and MODIS-Terra), SeaWiFS, MERIS, Sentinel-2, and unmanned aerial vehicles have contributed the most to these studies [9,[37][38][39][40][41][42]. The more recent and advanced satellites (e.g., Sentinel-3, launched in February 2016) provide added valuable resources for ocean color products, yet their recent deployment and, hence, their short record of historical data compared to earlier operational satellites (e.g., MODIS: 1999-present) puts them on the waiting list for future machine learning-based forecasting projects.…”
Section: Introductionmentioning
confidence: 99%